Experimental Study of the Unconstrained Melting of a Phase Change Material for Air-Conditioning Applications; [Étude Expérimentale de la Fusion Sans Contraintes D…Un Matériau À Changement de Phase Pour Des Applications de Conditionnement D…Air] - Ortega-Aguilera, R; Vasco-Calle, D; Jonathan Jesus-Cofre, T (Elsevier Ltd, 2023)
This study analyzed the RT8HC melting in a spherical vessel employing air as a heat transfer fluid. The phase change process was followed both visually and by thermal measurements. Photographs and thermographs allow the following phases evolution and melting mechanisms. We observed that the melting process was not symmetric around the vertical axis; implications of non-symmetric conditions on the melting mechanisms and heat transfer are discussed and analyzed. This work also includes the effects of outer water vapor condensation on heat transfer in the analyses. We proposed a mathematical model to quantify the heat flux that only requires humidity and temperature measurements and considers both heat convection and condensation effects. Results show that condensation significantly affects heat transfer during the initial stage of the melting process. Beside, these effects extend beyond the condensation time due to the liquid film draining from the spherical vessel surface. Regarding thermography, this technique may be a valuable tool for analyzing and following melting processes inside vessels; however, the presence of liquid film over the sphere affects the temperature measurements obtained from the thermograph analysis. This investigation provides relevant information about using phase change materials in cold thermal energy storage applications, latent thermal loads, and humidity control, which are essential aspects of air-conditioning system designs. © 2023 Elsevier Ltd and IIR